¿Implica la sensatez cierta calma? Análisis de la sophrosýne en los pasajes iniciales del Cármides - Budeguer, Andrés (Sapientia, 2024)
The article offers a critical reading of the initial passages of Plato’s Charmides (with particular attention to 153a –160e), focusing on the role of sophrosýnein the development of Socratic dialectic. Through an analysis of the introductory scene and the exchanges between Socrates, Critias, and Charmides, the philosophical relevance of the young interlocutor’s disposition for dialogue is highlighted. In particular, the first definition of sophrosýneas “a certain calmness” and the refutation carried out by Socrates are examined. It is argued that the refutation, far from being a merely negative exercise, has philosophical value and serves a propaedeutic function. The study invites a reconsideration of the status of aporetic dialogues, emphasizing their productivity in philosophical terms. Finally, a rational reconstruction of Socrates’ argument is proposed, and some implications for the broader understanding of Platonic thought are suggested